The effect of statin treatment on survival and on the use of healthcare resources among patients with acute myocardial infarction - Lien Nguyen; Unto Häkkinen; Henna Jurvanen (University of Oslo, 2018)
The aim of this study was to investigate the cost-effectiveness of statin use by newly hospitalised patients with acute myocardial infarction (AMI) in Finland. The data were from the PERFECT database of patients hospitalised for AMI and discharged in 1998-2012 in Finland. Selected patients had first-time AMI and had not used statins earlier (N=60 404). We generated a matched data set from statin non-users for statin users based on propensity matching analysis (N=28 412), which was also used. Statin use was defined as statins purchased within the first week after hospital discharge. Healthcare costs included costs of inpatient and outpatient hospital care, costs of nursing homes and costs of prescribed medicines (at 2011 prices). The follow-up time was one year. Logit and generalised linear models were used. We measured the effects of statin use as life years (LYs) gained and computed costs per LY gained. Both data were analysed for the entire period and for subperiods 1998-2001, 2002-2007 and 2008-2011, without discount rates and with a 3% discount rate. An average patient would gain 0.26-0.51 more years. The estimated costs per LY gained ranged between EUR 800 and 15 000. They were highest (EUR 12 000-15 000) in 1998-2001 by the matched data, but were actually savings in 2008-2011. The estimated costs indicate that statin use in treating AMI was very cost-effective. However, our rather long study period may suggest that the cost estimates per LY gained could be overestimated, as the life expectancy of AMI patients is likely shorter than that of the general population. Published: Online April 2018.